Does talent exist? A re-evaluation of the nature-nurture debate - Ward, P.; Belling, P.; Petushek, E.; Ehrlinger, J. (Routledge handbook of talent identification and development in sport, 2017)
Throughout history, knowledge and science have often progressed through dialectical debate. Logical arguments from one perspective are posed to counter those from another in the hopes of arriving at a holistic synthesis (e.g., see Sternberg, 1999). The nature-nurture debate has been one of the most enduring, frequently resurected by the media and scientists alike in an attempt to provide explanation for the fantastic feats of those we call `talented`. While a central feature of debate is to discuss the pros and cons of opposing views and polarizing stances, relatively few research efforts have sought genuine reconciliation between the extreme positions of nature and nurture (cf. Davids & Baker, 2007). W ith some exceptions, the modus operandi has been to advocate for one side of the debate while giving little credit to the merits of opposing arguments beyond token gestures. Debates on the science of talent are almost always theoretically and philosophically entrenched. We argue that perspectives are sometimes taken on one side of the debate to facilitate falsification in a systematic way but, more often, manufactured dichotomies lead to weak tests of a preferred theory, or are used as a guise to promote a preferred perspective incapable of providing unique explanations (see Feynman, 1974). In addition, despite best intentions to conduct `good science`, the tendency has been for research to be piecemeal rather than systematic, and disaggregated rather than systemic (Newell, 1973). Newell (1973) asserted that such practices result in ideological and theoretical differences becoming less clear and conflicting arguments being infrequendy resolved. The end product is unlikely to be a mature and cumulative science. The risk here is that the goals of science are relegated in priority and, as a result, science gives way to the process of telling stories based on data ex post facto. Such a path is unlikely to lead to much needed advances in the development of a useful theory of talent and limited capability to improve talent development.